What is the sum of all of the odd numbers from 1 to 59?

Answers

Answer 1
Answer:

Answer:

sum = 900

Step-by-step explanation:

The sum of all odd number can be solved using arithmetic progression formula.

Odd numbers are numbers that cannot be exactly divided by 2 .That means odd number have remainder when divide by 2.

The first odd number is 1

The second is  3

The sequence goes like this

1, 3, 5, 7, 9, 11, 13, 15, 17, 19 , 21 .................................59

a = 1

d = 2

where

a = first term

d = common difference

let us find the number of terms before finding the sum

nth term = a + (n - 1)d

59 = 1 + (n - 1)2

59 = 1 + 2n - 2

59 + 2 - 1 = 2n

60 = 2n

n = 60/2

n = 30

Sum = n/2(a+L)

where L = last term

sum = 30/2(1 + 59)

sum = 15(60)

sum = 900

Answer 2
Answer: arith. series for odd number
An = 1 + 2(n-1) ; A1 = 1

sum to n terms
Sn = (An + A1)n/2 ;
An=59, n = 29

Related Questions

A family wants to have 4 children. Design and do a simulation to determine the probability that, if they do have 4 children, they will have two boys and two girls. (Hint: Use coins.)
The value of a dirt bike decreases by 20% each year. If you purchased this dirt bike today for $500, to the nearest dollar how much would the bike be worth 5 years later?
A 6 ounce bag of raisians cosr$2.46 and a 8 ounce bag cost $3.20 which is better deal
Tanisha cut a triangle with angles of 62°, 30°, and 88° in three pieces so that each piece had one angle of the triangle. She arranged the three angles connected together such that the three corners of the triangle were all touching. What type of angle was formed and what does this show?
if you earn $8 per hour after taxes are taken out of your paycheck and your insurance is $200 a month, how many hours will you have to work to pay for insurance?

Find the measure of the missing angle

Answers

Answer:

45 degrees

Step-by-step explanation:

All triangles equal 180 degrees so your just add the two existing angles which gets you 135 then you do 180-135, therefore giving you 45

What is the sum of 2/10 and 3/10 in simplest form

Answers

The sum of 2/10 and 3/10 in simplest form is; 1/2

The sum of 2/10 and 3/10 is to be determined in simplest form;

Evidently, both fractions have the same denominator.

The question requires the sum and can be evaluated as follows;

  • 2/10 + 3/10

since, the LCM of the denominators is 10; we then have;

  • =(2+3)/10.

  • =5/10

= 1/2.

Read more:

brainly.com/question/17544795

it would be 1/2.
2/10 + 3/10 = 5/10, then simplify.

Adiya said that the first step to solving the quadratic equation x2 + 6 = 20x by completing the square was to divide 6 by 2, square that value, and add the result to both sides. Is Adiya’s solution method correct? Explain.

Answers

Answer:

No, it is incorrect.

Step-by-step explanation:

The quadratic equation is

x^2+6 = 20x or x^2-20x+6=0. To complete square we take the coefficient of x divided by 2, square that value and add the result to both sides. In the equation given the number to do the process is 20, not 6, then the solution method is incorect.

Answer:

NO it is not correct

Step-by-step explanation:

Adiya’s method is not correct. To form a perfect square trinomial, the constant must be isolated on one side of the equation. Also, the coefficient of the term with an exponent of 1 on the variable is used to find the constant in the perfect square trinomial. Adiya should first get the 20x term on the same side of the equation as x2. Then she would divide 20 by 2, square it, and add 100 to both sides.

What is the simplest form of the decimal 0.39 as a fraction?

Answers

0.39
The ans = 39/100

5 cm 13 cm and 12 cm is a right triangle

Answers

I think its not a right triangle because of the cm.

Yep, it is because it follows Pythagoras theorem

5²+12²=13²

What's the average rate of the graph from x = -2 to x = 0?​

Answers

Answer:

-2

Step-by-step explanation:

I hope this helps you :)

-KeairaDickson